Răspuns :
[(a:3-1):6+489]:25=26-2
[(a:3-1):6+489]:25=24
(a:3-1):6+489=24*25
(a:3-1):6+489=600
(a:3-1):6=600-489
(a:3-1):6=111
a:3-1=111*6
a:3-1=666
a:3=666+1
a:3=667
a=667*3
a=2001
[(a:3-1):6+489]:25=24
(a:3-1):6+489=24*25
(a:3-1):6+489=600
(a:3-1):6=600-489
(a:3-1):6=111
a:3-1=111*6
a:3-1=666
a:3=666+1
a:3=667
a=667*3
a=2001
[(a : 3 - 1) : 6 + 489] : 25 + 2 = 26
[(a : 3 - 1) : 6 + 489] : 25 = 26 - 2
[(a : 3 - 1) : 6 + 489] = 24 * 25
(a : 3 - 1 : 6 = 600 - 489(a : 3 - 1) = 111 * 6
a : 3 = 666 + 1
a = 3 * 667
a = 2001
[(a : 3 - 1) : 6 + 489] : 25 = 26 - 2
[(a : 3 - 1) : 6 + 489] = 24 * 25
(a : 3 - 1 : 6 = 600 - 489(a : 3 - 1) = 111 * 6
a : 3 = 666 + 1
a = 3 * 667
a = 2001